Study on Mechanical Properties and Nonlinear Strength Model of Deep Water-Sensitive Rock in Xianglu Mountain Tunnel. (9th August 2022) - Ren, Mingyang; Wu, Xuyang; Zhang, Longyun; Pan, Junkui; Li, Ningjing
Abstract : The complex mechanical properties of deep water-sensitive rocks during construction bring great challenges to the construction and stability analysis of underground engineering in water-sensitive strata. Taking Xianglu Mountain Tunnel in the Central Yunnan Water Diversion Project as the engineering background, the mechanical properties of two types of water-sensitive rocks including limestone and silty mudstone were studied through laboratory tests, and a nonlinear strength model based on Hoek-Brown criterion was proposed. The results show that (1) the stress-strain curves of deep limestone and silty mudstone have significant strain softening characteristics and brittle-ductile transformation trend. Compared with limestone, silty mudstone has stronger ductility and lower critical confining pressure for brittle-ductile transformation; (2) the dilation effect of rock is affected by both confining pressure and plastic deformation. Under the same confining pressure and plastic deformation, the dilation characteristic of limestone is more evident than that of silty mudstone; (3) the Hoek-Brown criterion can describe the nonlinear strength characteristics of deep rock well. The evolution law of strength parameters m b and s with modified plastic shear strain conforms to the negative exponential function, while the relationship between strength parameter a and modified plastic shear strain satisfies cubic polynomial function; (4) the simulation results based on the nonlinear strength model are consistent with the test results, and the established strength model has high reliability. The research results can provide a basis for the stability analysis of the Xianglu Mountain Tunnel and the optimal design of the supporting structure and can also provide a reference for the study of the mechanical characteristics of the deep rocks in water-sensitive strata.